Celular features of Curcuma xanthorhiza, Zingiber cassumunar, Phyllanthus niruri and other medicinal plants - Wiart, C. (Forest Research Institute Malaysia (FRIM), 2014)
The growing use of medicinal plants in the health and pharmaceutical industries has prompted the return of the study of pharmcognosy. Pharmacognosy or, in Greek, "the science of poisons" is a discipline of pharmaceutical science. Its main aim is to ensure the identity and quality of drugs of natural origin. In this presentation, the authors wish to show the application of modern microphotographic techniques in ascertaining the nature of plant powders by presenting as examples the cellular patterns of Curcuma xanthorrhiza, Zingiber cassumunar and Phyllanthus niruri. Several types of cells are presented and their value as indicators is introduced.